Utilization of multi-recycled aggregates from different concrete sources and effect of silica fume in multi-recycled concrete mixtures: an urban mining practice - Katranci, Ali Baris; Ozdogru, Emine; Ozen, Omer Can; Cakir, Ozgur (TAYLOR & FRANCIS LTD, 2026)
This study presents a comparative experimental procedure examining the multiple reuses of concrete waste from a realistic perspective, aiming to enhance the performance of the resulting product. Three distinct mixtures were subjected to three consecutive cycles to evaluate two key parameters: the effect of source concrete quality using laboratory-produced and real-case construction and demolition waste (CDW) and the influence of silica fume (SF), assessed by comparing 0% and 5% SF replacement. The physical and mechanical properties of the aggregates derived from each series were evaluated. Additionally, the micro- and macrostructural characteristics of the concretes produced from these aggregates were investigated. According to the results, the compressive strength of the concrete specimens incorporating CDW-based aggregate and SF increased by 18.03% from the first to the third cycle, outperforming both the reference and non-SF counterparts. These findings underline the importance of multi-recycling real-case CDW for realistic and sustainable concrete production.
Keywords: Construction and demolition waste; multi-recycled aggregate concrete; closed loop recycling; waste management; end-of-waste criteria; urban mining; 3 GENERATIONS; PERFORMANCE; WASTE; Construction & Building Technology; Science & Technology - Other Topics; Materials Science